Assessing New Methods to Optimally Detect Episodes of Non-metabolic Heart Rate Variability Reduction as an Indicator of Psychological Stress in Everyday Life: A Thorough Evaluation of Six Methods - Brown, Stephen B. R. E.; Brosschot, Jos F.; Versluis, Anke; Thayer, Julian F.; Verkuil, Bart (Frontiers in Neuroscience, 2020)
Frequent or chronic reduction in heart rate variability (HRV) is a powerful predictor of cardiovascular disease, and psychological stress has been suggested to be a co-determinant of this reduction. Recently, we evaluated various methods to measure additional HRV reduction in everyday life and to relate these reductions to psychological stress. In the current paper, we thoroughly evaluate these methods and add two new methods in both newly-acquired and reanalyzed datasets. All of these methods use a subset of 24 hours’ worth of HRV and movement data to do so: either the first 10 minutes of every hour, the full 24 hours, a combination of 10 minutes from three consecutive hours, a classification of level of movement, the data from day n to detect episodes in day n + 1, or a range of activities during lab calibration. The method that used the full 24 hours’ worth of data detected the largest percentage of episodes of reduced additional HRV that matched with self-reported stress levels, making this method the most promising, while using the first 10 minutes from three consecutive hours was a good runner-up.